2022
DOI: 10.1021/acsomega.2c04766
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Modulation of Carbon-Dot Optical Sensing Attributes through a Reduction Pathway

Abstract: Oxidized/reduced carbon dots (CDs) with tunable optical features have emerged as a new class of CDs having a common "molecular origin" but different fluorescence (FL) behaviors. In the present work, using "banana peel" as a sole carbon source followed by doping with fluorine (F), boron (B), and nitrogen (N) over CDs, banana peel-derived carbon dots (BP-CDs) were synthesized using a well-known hydrothermal synthesis method. Moreover, as-synthesized BP-CDs were further reduced to "rBP-CDs" by NaBH 4 . At post re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Fig. 3d shows the intensity variation vs. PA concentrations plot, revealing a linear relationship (with an excellent correlation coefficient, R 2 , of 0.9976), and a LOD of 104 nM determined using eqn (2). The value of the quenching constant was found to be 2.8 Â 10 À2 M À1 calculated using eqn (3).…”
Section: Fluorescence-based Pa Detection With Tf-cdsmentioning
confidence: 81%
See 1 more Smart Citation
“…Fig. 3d shows the intensity variation vs. PA concentrations plot, revealing a linear relationship (with an excellent correlation coefficient, R 2 , of 0.9976), and a LOD of 104 nM determined using eqn (2). The value of the quenching constant was found to be 2.8 Â 10 À2 M À1 calculated using eqn (3).…”
Section: Fluorescence-based Pa Detection With Tf-cdsmentioning
confidence: 81%
“…In the past decade, carbon dots (CDs) have been proven to be an efficient fluorescent (FL) sensor due to their exceptional and stable luminescence properties with minimal photobleaching and excellent biocompatibility. [1][2][3] The abundance of various precursor molecules and simple synthetic routes with ease of surface modification make CDs quite versatile and highly useful in myriad applications such as sensing, 4 bio-imaging, 5 drug delivery, 6 energy storage, 7 photodynamic therapy, 8 photocatalysis, 9 etc. Recent studies have shown that the CD structure could be more effectively controlled by the wise selection of the carbon precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional fluorescent materials, CDs exhibit low toxicity and high biocompatibility, thereby reducing the risk of side effects when they enter the body [47,48]. Additionally, most CDs are water-soluble, which simplifies sample preparation by avoiding the need for complex pre-treatment procedures.…”
Section: Biological Imagingmentioning
confidence: 99%